Immunoproteomic Analysis And Serodiagnosis Of Salmonella Enteretica Typhi And Invasive Non-Typhoidal Salmonella Infections Using Differentially Extracted Whole Cell Bacterial Protein - Abdul Lateef Khan, Khairunnisa (2023)
Typhoid fever is a potentially fatal infectious disease caused by Salmonella Typhi. The disease is endemic in developing countries, but alarming number of cases linked to domestic sources have been reported in industrialized countries. The clinical presentation of typhoid fever is highly variable and often overlap with other acute undifferentiated febrile illnesses (AUFI). Hence, accurate identification of isolates is important for effective epidemiological intervention. The development of rapid, costeffective diagnostic test is also crucial for early life saving treatment. Therefore, comparative analysis was performed to characterize protein profiles of two differentially extracted Salmonella serovars by sodium dodecyl sulphatepolyacrylamide gel electrophoresis (SDS-PAGE). Separation of protein into three different extractions revealed discriminative protein profiles between the two strains which provided an effective adjunct that can be used as a tool for protein serotyping. A standardized protocol of the dot Enzyme Immunoassay (dot EIA) with differentially extracted antigens derived from S.Typhi and S.spp was established for definitive and differential diagnosis of typhoid fever. The performance of the test was encouraging with high sensitivity and specificity. Following the successful development of 'TYPHOIDYNE μSpot M-Ag Arrays, the antigenic components of the differentially extracted proteins were further characterized by western blot (WB) assay.